Solid particle erosive wear behaviour of Eulaliopsis binata fiber reinforced epoxy composite. (April 2021) - Pradhan, Subhrajit; Acharya, Samir K
In the present work, Eulaliopsis binata, a natural fiber collected from the eastern part of India is taken as a reinforcement with epoxy resin to develop a new class of polymer composite material, which has been unexplored till date for tribological applications in the composite industry. Different characterization studies of the fiber such as SEM, EDS, XRD are carried out to astern its potential to be used as a fiber in composite. Short Eulaliopsis binata fiber of different weight percent (10, 20, 30, and 40) is incorporated in neat epoxy and polymer composites are fabricated using the hand lay-up method. Solid particle erosion behavior of the fabricated composites is studied with four different impact velocities (48, 72, 82, 116 m/s) and impinging angles (30°, 45°, 60°, 90°). Improved erosion wear resistance is exhibited by the composites after the addition of Eulaliopsis binata fiber to neat epoxy. In addition, the inclusion of fiber altered the erosion behavior of neat epoxy from brittle to semi ductile nature. The impact velocity of the erodent particles also shows significant effect on the erosion behavior of the developed composites. The eroded surfaces of the worn samples are analyzed with SEM to ascertain the failure mechanism of the developed composites.